Match demands of professional rugby football codes: A review from 2008 to 2015 - Hogarth, L. W.; Burkett, B. J.; McKean, M. R.; Gabbett, T.; Kraak, W. (International Journal of Sports Science & Coaching, 2016)
Rugby football codes have continually increased in popularity and are played professionally around the world at domestic, national and international level. Coaching professionals can use the findings of this review to guide training practices for the professional rugby football player, particularly those players who may be competing concurrently or transferring between codes. The development of repeated high-intensity exercise ability should be a key emphasis of training programmes especially for players who are aiming to compete at higher competition standards. Importantly, there are considerable differences in repeated high-intensity exercise demands of match-play for different positional groups. For greatest transference to match performance, training programs should replicate the frequency and duration of repeated high-intensity exercise bouts in addition to the relative contribution of high-intensity running, tackling and physical collisions. Training programmes should not neglect developing players' prolonged high-intensity running ability as highspeed running efforts may occur separately from repeated high-intensity exercise bouts and likely place considerable demands on rugby football players, particularly in rugby sevens competition. Rugby football players have been shown to experience transient fatigue patterns during match-play where teams may be susceptible to conceding points or sustaining injury. Improved physical conditioning strategies may reduce development of match-fatigue; however, research is yet to investigate the influence of fitness levels and team strategies. A better understanding of these factors and how they interact with match-fatigue will assist with the improvement of training practices for professional rugby football players. ABSTRACT FROM AUTHOR